Technological Innovation in Islamic Education (Exploring the Impact of Gamification-Based Media on Enhancing Elementary School Students' Learning Creativity) - Komariyah, Komariyah; Hasan, Muasrul; Chumaidah, Arofatul; Huda, Nuril; Utami, Sri (Maharot : Journal of Islamic Education, 2024)
This study aims to determine the basic concepts and impacts of gamified media in enhancing students' learning creativity in elementary schools. The approach used in this research is qualitative with a literature review type. The data collection technique used is documentation with interactive analysis according to Miles & Huberman. The results show that the concept of gamification in learning utilizes technology and IT-based media to increase student engagement and learning outcomes through gaming elements. In elementary schools, gamification stimulates students' interest, enhances creativity, and provides an interactive learning experience. The positive impact is that students become more creative with challenges and rewards from gamification, aiding in the development of creative thinking skills.